Identification and functional characterization of AsWRKY9, a WRKY transcription factor modulating alliin biosynthesis in garlic (Allium sativum L.) - Jiaying Wu; Min Li; Wanni Wang; Yiren Su; Jie Li; Jiaxin Gong; Xianfeng Meng; Chenyuan Lin; Qiantong Zhang; Yanyan Yang; Chunyan Xu; Limei Zeng; et al. (BMC Biology)
Abstract Background The variations in alliin content are a crucial criterion for evaluating garlic quality and is the sole precursor for allicin biosynthesis, which is significant for the growth, development, and stress response of garlic. WRKY transcription factors are essential for enhancing stress resistance by regulating the synthesis of plant secondary metabolites. However, the molecular mechanisms regulating alliin biosynthesis remain unexplored. Here, we report for the first time that a WRKY family transcription factor regulates the expression of a key enzyme gene in the alliin biosynthesis pathway, enhancing the accumulation of alliin. Results AsWRKY9 was most highly expressed in garlic leaves, and its expression was significantly upregulated at various time points following leaf injury. Moreover, we established an improved garlic callus induction medium based on MS medium with 1.5 mg/L 2,4-D and 0.5 mg/L NAA, suitable for “PiZi” garlic bulbils. In transgenic callus overexpressing AsWRKY9, the transcription level of the key enzyme flavin-containing monooxygenase gene (AsFMO1) significantly higher, as did its enzymatic activity compared with the control. Subcellular localization revealed that AsWRKY9 is located in the nucleus. The promoter sequence of AsFMO1 was then obtained using genomee walking. Yeast one-hybrid (Y1H) and dual-luciferase assays (LUC) confirmed that AsWRKY9 interact with the AsFMO1 promoter. Further verification by electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation qPCR (ChIP-qPCR) confirmed that AsWRKY9 interacts by binding to the W-box site on the AsFMO1 promoter. Compared to the control, the alliin content in the transgenic callus overexpressing AsWRKY9 was significantly increased, thus confirming the activation of the alliin biosynthesis pathway and enhancing the accumulation of alliin in garlic. Conclusions Our study reveals the crucial role of AsWRKY9 in alliin biosynthesis, filling a gap in the complex transcriptional regulation of the alliin biosynthetic pathway. It provides a new molecular breeding strategy for developing garlic varieties with high alliin content.